A concepção dos alunos sobre a disciplina física no ensino médio de uma escola pública na cidade de Manaus - Santos, Patrik Marques dos (2013)
The physics discipline in high school is still seen, by many students, as something unrelated to everyday life, which relates, in a way, more mathematical procedures than the phenomena. With this, this research proposed to analyze the students' conception about the physics of the high school in a public school of Manaus, understanding the objections and difficulties about this discipline, because in researches carried out in Brazil and in other places of the world identified aversion by this discipline, showing concomitant elements in both: the mathematics used in the formalization of the study and the contextualization. Also, this work aimed to provide data on the situation found in the city of Manaus, since there are no records related to the researched theme, which further strengthens the need to develop more work in the area, so as to build solid foundations for future discussions to Physics Education in the city. Aware of this, it was assumed that the assessments carried out on a state, national and international basis, in order to visualize, initially, the panorama of schools in the city in the discipline and to elucidate the elements signaled by them, and thus add to the understanding of the study. developed in this work. In addition, the following were used to support the research: the Curriculum Parameters - PCN +, PCNEM and the Curricular Guidelines of the Secretary of Education of Amazonas - leading the look of the research to a qualitative and systematic context of the knowledge and authors who discuss how students should learn Science, corroborating their research and experiences with this study. The work was based on the sample of a school located in the city center, in the afternoon shift, carried out only with high school students, totaling 560 students. A semi-structured questionnaire was developed for these students in order to understand their conception of the subject of Physics. And, from this, the results obtained were systematized and compared with research related to the same theme, which were part of other realities found in the country and outside of it. KEYWORD: Conception, Difficulty, Physics.